Genome-wide association study for systemic lupus erythematosus in an egyptian population - Elghzaly, Ashraf A.; Sun, Celi; Looger, Loren L.; Hirose, Misa; Salama, Mohamed; Khalil, Noha M.; Behiry, Mervat Essam; Hegazy, Mohamed Tharwat; Hussein, Mohamed Ahmed; Salem, Mohamad Nabil; Eltoraby, Ehab; Tawhid, Ziyad; et al. (Frontiers in Genetics, 2022)
Systemic lupus erythematosus (SLE) susceptibility has a strong genetic component. Genome-wide association studies (GWAS) across trans-ancestral populations show both common and distinct genetic variants of susceptibility across European and Asian ancestries, but many other ethnic populations remain underexplored. We conducted the first SLE GWAS on Egyptians–an admixed North African/Middle Eastern population–using 537 patients and 883 controls. To identify novel susceptibility loci and replicate previously known loci, we performed imputation-based association analysis with 6,382,276 SNPs while accounting for individual admixture. We identified a novel genome-wide significant locus near IRS1/miR-5702 (𝑃corrected =1.98x10-8) and eight suggestive loci (𝑃corrected <1.0x10-5). We also replicated 154 previously known loci with at least one associated (𝑃corrected <0.05) nearby SNP, including PPARD, TNOP3, and ITGAM with 𝑃corrected <1.0x10-5. SNPs correlated (r2 > 0.8) with lead SNPs from four novel loci (ARMC9, DIAPH3, IFLDT1, and ENTPD3) were associated with differential gene expression (3.5x10-95< p < 1.0x10-2) across diverse tissues. The loci are involved in cellular proliferation and invasion – pathways prominent in lupus and nephritis. Our study highlights the utility of GWAS in an admixed Egyptian population for delineating new risk loci and for understanding SLE pathogenesis.